Implementasi Kebijakan Program Jak-Lingko Transjakarta dalam Upaya Perbaikan Transportasi Publik di Pinang Ranti Jakarta Timur - Sianturi, Widya Rhenata; Samudra, Azhari Aziz; Robby, Uchaimid Biridlo’I (ANTASENA: Governance and Innovation Journal, 2023)
Jak-lingko is a program established bye the DKI Jakarta Provincial Goverment through PT,Transjakarta as thye executor of the Jak-lingko program. As regulated in Pergub Number 110 of 2003 and Pergub Number 96 of 2018 concerning the new transportation system. To identity policy implementation using success variables to achieve the objectives of policy implementation or program implementation (Communication, Resources, Disposition, Bureaucratic Structure) are indicators of policy implementation proposed by George Edward III. This study discusses the Implementation of Jak-Lingko Program Policies in Efforts to Improve Public Transportation in Pinang Ranti East Jakarta in 2018. The type of research used is qualitative research, data collection techniques, namely observation, interviews and documentation related to research. The results of this study explain that from the beginning the implementation of the jak-lingko enviroment program has been quite effective but it is indeed necessary to realize or deliver more about the jak-lingko environment program to the people of Jakarta